NUMERICAL AND GRAPHICAL RESULTS OF FINITE SYMMETRIC INVERSE (I_{n}) AND FULL (T_{n}) TRANSFORMATION SEMIGROUPS - Kehinde, R.; Abdulazeez, O. H. (FUDMA JOURNAL OF SCIENCES, 2021)
Supposed  is a finite set, then a function is called a finite partial transformation semigroup , which moves elements of  from its domain to its co-domain by a distance of  where . The total work done by the function is therefore the sum of these distances. It is a known fact that  and . In this this research paper, we have mainly presented the numerical  solutions of the total work done, the average work done by functions on the finite symmetric inverse semigroup of degree ,  and the finite full transformation semigroup of degree ,  as well as their respective powers for a given fixed time  in space. We used an effective methodology and valid combinatorial results to generalize the total work done, the average work done and powers of each of the transformation semigroups. The generalized results were tested by substituting small values of  and a specified fixed times  in space. Graphs were plotted in each case to illustrate the nature of the total work done and the average work done. The results obtained in this research article have an important application in some branch of physics and theoretical computer science